2015
DOI: 10.2174/1568026615666150827094500
|View full text |Cite
|
Sign up to set email alerts
|

Gold(III) Complexes in the Oncological Preclinical Arena: From Aminoderivatives to Peptidomimetics

Abstract: In the last decade, we have been developing some gold(III) derivatives showing interesting antitumor properties and reduced systemic and renal toxicity, compared to the clinically-established reference drug cisplatin. Starting from the rationale at the base of our investigations, this review has been divided into two sections, with respect to our patented first- (aminoderivatives) and secondgeneration (peptidomimetics) potential drugs. Every section describes the in vitro and in vivo anticancer activity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 112 publications
(194 reference statements)
1
24
0
Order By: Relevance
“…[11,15,53,69] For this class of complexes, DNA does not appear to be am ajor target, despite the great affinity for the isolatedD NA moleculea nd the capability to inhibit both RNA and DNA synthesis in ad ose-independent way,inc ontrast to what has been observed for cisplatin. [11,15,53,69] For this class of complexes, DNA does not appear to be am ajor target, despite the great affinity for the isolatedD NA moleculea nd the capability to inhibit both RNA and DNA synthesis in ad ose-independent way,inc ontrast to what has been observed for cisplatin.…”
Section: Ex Vivo Toxicitymentioning
confidence: 91%
See 2 more Smart Citations
“…[11,15,53,69] For this class of complexes, DNA does not appear to be am ajor target, despite the great affinity for the isolatedD NA moleculea nd the capability to inhibit both RNA and DNA synthesis in ad ose-independent way,inc ontrast to what has been observed for cisplatin. [11,15,53,69] For this class of complexes, DNA does not appear to be am ajor target, despite the great affinity for the isolatedD NA moleculea nd the capability to inhibit both RNA and DNA synthesis in ad ose-independent way,inc ontrast to what has been observed for cisplatin.…”
Section: Ex Vivo Toxicitymentioning
confidence: 91%
“…Despite these restrictions, it is still administered to patients to treat testicularc ancera nd, in combination with other chemotherapeutics, some ovarian, small-cell lung, bladder,a nd breast tumors. [11] Moreover,n either cross-resistance nor the main drawbacks of cisplatin-based therapy were detected.I ndeed, in recenty ears, it was demonstrated that Au III -dithiocarbamato complexes exploit am echanism of action different from that of the clinically established platinum drugs. [7][8][9] In particular, research has focusedonthe synthesis of newc omplexesw ith better selectivity for cancerous cells and,consequently,with less side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless some recent examples of less common transition metal intercalators have emerged in the literature. For example, gold complexes have been relatively successful in medicinal chemistry [69,70,71], although most active anticancer complexes do not target DNA [72,73,74]. Recently reported macrocyclic gold(III) complexes that incorporated a quinoxaline moiety to promote DNA intercalation demonstrated cytotoxic activity [75].…”
Section: Other Metalsmentioning
confidence: 99%
“…Since gold(III) is isoelectronic to platinum(II) and both metals preferentially generate square planar complexes (d 8 system) a number of gold(III) complexes were synthesized and tested as an alternative to the anticancer drug cisplatin (22)(23)(24)(25)(26)(27). Due to the fact that the gold(III) has high reduction potential, a range of strategies has been applied in order to obtain gold(III) complexes with sufficient stability under physiologically relevant conditions.…”
Section: Introductionmentioning
confidence: 99%